Causes of increased pollen exposure during Saharan-Sahel dust intrusions. (1st September 2021) - Rojo, Jesús; Moreno, José María; Romero-Morte, Jorge; Lara, Beatriz; Elvira-Rendueles, Belén; Negral, Luis; Fernández-González, Federico; Moreno-Grau, Stella; Pérez-Badia, Rosa
Abstract: Airborne particulate matter such as mineral dust comes mainly from natural sources, and the African regions of Sahara and Sahel originate large amounts of the aerosols dispersed worldwide. There is little knowledge about the influence of dust episodes on airborne pollen concentrations, and although the centre and southeast of the Iberian Peninsula are frequently affected by dust intrusions, until now, no specific works have analysed the effect of these episodes on airborne pollen concentrations in these areas. The aims of this study were to analyse the simultaneous occurrence of airborne pollen peaks and Saharan-Sahel dust intrusions in the central and south-eastern Iberian Peninsula, and to study the weather conditions – air mass pathways and conditions of air temperature, relative humidity and atmospheric pressure – that influence the airborne pollen concentrations during dust episodes. The results showed that the rise in airborne pollen concentrations during dust episodes is apparent in inland Iberian areas, although not in coastal areas in the southeast where pollen concentrations are even observed to decrease, coinciding with prevailing easterly winds from the sea. Total pollen concentrations and specific pollen types such as Olea, Poaceae and Quercus showed an increase in the central Iberian Peninsula during dust episodes when two meteorological phenomena concur: 1) prevailing winds from extensive areas of major wind-pollinated pollen sources over a medium or short distance (mainly from western and southwestern areas); and 2) optimal meteorological conditions that favour pollen release and dispersal into the atmosphere (mainly high temperatures and subsequently low humidity in central areas). Both conditions often occur during the Saharan-Sahel dust intrusions in the centre. Maximum pollen peaks are therefore most likely to occur during dust episodes in the central Iberian Peninsula, thus dramatically increasing the risk of outbreaks of pollinosis and other respiratory diseases in the population. Graphical abstract: Image 1 Highlights: The pollen exposure due to dust events was studied in the Iberian Mediterranean area. The main pollen peaks occurred in inland Iberian areas during Saharan dust episodes. Prevailing winds from extensive wind-pollinated sources were partly responsible. Meteorological conditions during dust episodes favoured pollen emission and dispersal. Conditions favouring pollen dispersal during dust events often occur in inland areas. Abstract : The rise in airborne pollen concentrations during Saharan dust intrusions is clearly apparent in inland Iberian areas caused by the wind patterns and the optimal atmospheric conditions for pollen dispersal.